Contribution to remediation of brackish lagoon: 3D simulation of salinity, bottom currents and resuspension of bottom sediments by strong winds. (5th January 2019) - Alekseenko, E.; Roux, B.
Abstract: This work concerns the modelling and numerical simulation of the 3D salinity and current distribution in a very shallow Mediterranean lagoon subject to strong winds which create intensive resuspension of polluted bottom sediments. We consider wind speeds of 10 m/s and 20 m/s in the two dominant wind directions (N-NW and S-SE). This study is made for different scenarios of flow exchanges with the surrounding hydrosystems: a brackish lagoon on the North (the Etang de Berre), the Cadiere River on the East, and a brackish channel on the South (the Rove channel). The bottom shear stress ( B S S ) are compared to the B B S threshold given in the literature in terms of the bottom roughness. It permits to determine which kind of bottom sediments (muds and sands) will be resuspended by each wind. The bottom currents permit to predict in which direction the suspended sediments will be moved and where are the sedimentary deposit zones. It provides a guide for the specialists of remediation of the lagoon for a mechanical extraction of sediments in such zones. In addition, numerical experiments have been performed to understand how the salinity distribution depends on the flow exchanges with the two brackish surrounding hydrosystems. This new knowledge will permit the owner of this lagoon to know how to maintain efficiently the level of salinity in the suitable range.